Physical performance strongly predicts all-cause mortality risk in a real-world population of older diabetic patients: machine learning approach for mortality risk stratification - Montesanto, Alberto; Lagani, Vincenzo; Spazzafumo, Liana; Tortato, Elena; Rosati, Sonia; Corsonello, Andrea; Soraci, Luca; Sabbatinelli, Jacopo; Cherubini, Antonio; Conte, Maria; Capri, Miriam; Capalbo, Maria; et al. (Frontiers in Endocrinology, 2024)
Background: Prognostic risk stratification in older adults with type 2 diabetes (T2D) is important for guiding decisions concerning advance care planning. Materials and Methods: A retrospective longitudinal study was conducted in a real-world sample of older diabetic patients afferent to the outpatient facilities of the Diabetology Unit of the IRCCS INRCA Hospital of Ancona (Italy). 1001 T2D patients aged more than 70 years were consecutively evaluated by a multidimensional geriatric assessment, including physical performance evaluated using the Short Physical Performance Battery (SPPB). The mortality was assessed during a 5 years follow-up. We used the automatic machine-learning (AutoML) JADBio platform to identify parsimonious mathematical models for risk stratification.Results: Of 977 subjects included in the T2D cohort the mean age was 76.5 (SD: 4.5) years and 454 (46.5%) were men. Mean follow-up time was 53.3 (SD:15.8) months, and 209 (21.4%) patients died by the end of the follow-up. The JADBio AutoML final model included age, sex, SPPB, chronic kidney disease, myocardial ischemia, peripheral artery disease, neuropathy and myocardial infarction. The bootstrap corrected concordance index (c-index) for the final model was 0.726 (95% CI: 0.687 -0.763) with SPPB ranked as the most important predictor. Based on penalized Cox regression model the risk of death per unit of time for a subject with a SPPB score lower than five points was 3.35 times that for a subject with a score higher than 8 points (P-value<0.001). Conclusions: Assessment of physical performance needs to be implemented in clinical practice for risk stratification of T2D older patients.